2018
DOI: 10.1158/0008-5472.can-18-0484
|View full text |Cite
|
Sign up to set email alerts
|

EWS/ETS-Driven Ewing Sarcoma Requires BET Bromodomain Proteins

Abstract: The EWS/ETS fusion transcription factors drive Ewing sarcoma (EWS) by orchestrating an oncogenic transcription program. Therapeutic targeting of EWS/ETS has been unsuccessful; however, identifying mediators of the EWS/ETS function could offer new therapeutic options. Here, we describe the dependency of EWS/ETS-driven transcription upon chromatin reader BET bromdomain proteins and investigate the potential of BET inhibitors in treating EWS. EWS/FLI1 and EWS/ERG were found in a transcriptional complex with BRD4,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 47 publications
(60 reference statements)
5
69
1
Order By: Relevance
“…We also confirmed AURKA kinase inhibition by alisertib and concomitant MYC repression, consistent with prior studies . Our work does not preclude other biological impacts of alisertib and I‐BET151 on ES biology; in fact, we do confirm that BRD4 inhibition does impair EWS‐FLI1‐mediated transcriptional activation as shown by I‐BET151's repression of NR0B1, consistent with recent data . Nonetheless, our data does demonstrate a mechanism of synergy between the two drugs, further augmented by use of chemotherapy such as vincristine.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We also confirmed AURKA kinase inhibition by alisertib and concomitant MYC repression, consistent with prior studies . Our work does not preclude other biological impacts of alisertib and I‐BET151 on ES biology; in fact, we do confirm that BRD4 inhibition does impair EWS‐FLI1‐mediated transcriptional activation as shown by I‐BET151's repression of NR0B1, consistent with recent data . Nonetheless, our data does demonstrate a mechanism of synergy between the two drugs, further augmented by use of chemotherapy such as vincristine.…”
Section: Discussionsupporting
confidence: 92%
“…BRD4 is active and oncogenic in cancers by promoting expression of multiple targets, including CDK4/6, MCL1, BCL2, MYC,, and AURKA . BRD4 has been more recently shown to be critical for EWS‐FLI1‐directed transcriptional reprogramming . BRD4 inhibitors showed some preclinical efficacy against ES; while BRD4 inhibition alone could not induce ES tumor regression in these studies, the data did show BRD4 inhibition could inhibit tumor formation .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Prior work indicates that BET bromodomain inhibitors and degraders may have applications in Ewing Sarcoma. 24 To investigate potential synergy between direct and indirect repression of the EWS/FLI transcriptional program, we evaluated degradation of EWS/FLI in combination with BET bromodomain degradation. We observed that dBET6, a CRBN-recruiting, pan-BET bromodomain degrader, 25 synergized strongly with VHL-mediated EWS/FLI degradation (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%